Website-Based Information Management and Temperature and Air Quality Monitoring System Using ESP32 - Eliza Fitri Ramadanti; Ahmad Taqwa; Adewasti Adewasti (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
The development of Internet of Things (IoT) technology has created new opportunities for improving information management and environmental monitoring in healthcare facilities. Puskesmas Makrayu Palembang currently relies on conventional information dissemination methods, resulting in limited accessibility and inefficient information updates. This study aims to design and implement a website-based information management and environmental monitoring system using Arduino Uno as the main controller and ESP32 as the communication module. The proposed system integrates a website-based information management platform, Firebase Realtime Database, P10 LED matrix display, DHT22 temperature sensor, MQ135 air-quality sensor, and buzzer notification mechanism within a unified IoT architecture. The research adopted a system development approach consisting of literature study, field observation, system requirement analysis, system design, implementation, and testing. The implementation results demonstrated that website data synchronization, Firebase communication, ESP32 connectivity, LED matrix display operation, sensor integration, and overall system integration were successfully achieved during prototype testing. Information entered through the website could be displayed correctly on the running-text display in real time, while environmental information obtained from the DHT22 and MQ135 sensors could be processed and displayed simultaneously. The evaluation focused on functional verification of communication, synchronization, display operation, and sensor integration within a prototype environment. However, the system was evaluated only at the prototype level due to limited deployment opportunities and research time constraints, and therefore does not yet fully represent continuous operational conditions in healthcare facilities. Consequently, aspects such as long-term ESP32–Firebase communication stability, data transmission latency, system consistency under prolonged operation, and performance under high communication loads were not evaluated in this study. The proposed system nevertheless provides a practical foundation for integrated healthcare information management and environmental monitoring applications in primary healthcare facilities.